Rational screening of biomineralisation peptides for colour-selected one-pot gold nanoparticle syntheses. Issue 1 (20th August 2018) - Tanaka, M.; Takahashi, Y.; Roach, L.; Critchley, K.; Evans, S. D.; Okochi, M.
Abstract : Biomineralisation peptides that facilitate the one-pot synthesis of gold nanoparticles (AuNPs) with selected optical properties, were screened using a coherent peptide-spotted array consisting of a AuNP binding peptide library. Abstract : Biomineralisation peptides that facilitate the one-pot synthesis of gold nanoparticles (AuNPs) with selected optical properties, were screened using a coherent peptide-spotted array consisting of a AuNP binding peptide library. As the biomineralised AuNPs were captured on each peptide spot, analysis of the images provided information on their collective optical properties.